2022
DOI: 10.1038/s41598-022-05303-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic antibacterial minerals: harnessing a natural geochemical reaction to combat antibiotic resistance

Abstract: The overuse of antibiotics in clinical and livestock settings is accelerating the selection of multidrug resistant bacterial pathogens. Antibiotic resistant bacteria result in increased mortality and financial strain on the health care and livestock industry. The development of new antibiotics has stalled, and novel strategies are needed as we enter the age of antibiotic resistance. Certain naturally occurring clays have been shown to have antimicrobial properties and kill antibiotic resistant bacteria. Harnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Pseudomonas aeruginosa, and Candida albicans // Pathogens 9 (4) Спрос на новые антимикробные препараты высок в медицине, ветеринарии, сельском хозяйстве и др. Однако многие классические препараты на основе стероидов, олиго-/макроциклических лактонов и антибиотиков имеют ряд недостатков: негативные для здоровья последствия, потенциальные экологические риски и т.д.…”
Section: Gh Nersisyan Ma Melkumyan Bg Babayan Am Grigoryan Al Grigory...unclassified
See 1 more Smart Citation
“…Pseudomonas aeruginosa, and Candida albicans // Pathogens 9 (4) Спрос на новые антимикробные препараты высок в медицине, ветеринарии, сельском хозяйстве и др. Однако многие классические препараты на основе стероидов, олиго-/макроциклических лактонов и антибиотиков имеют ряд недостатков: негативные для здоровья последствия, потенциальные экологические риски и т.д.…”
Section: Gh Nersisyan Ma Melkumyan Bg Babayan Am Grigoryan Al Grigory...unclassified
“…with some organic plant and animal sourced substances of target effects, such as like propolis, plant essential oils, waxes and also fungi bioactive components, etc. [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…A recent scientific report showed that synthetic smectite clay minerals and Fe-sulfide microspheres have antimicrobial properties and kill antibiotic resistant bacteria including E. coli and Enterococcus spp. (Morrison et al, 2022) but we did not inquire about the use of these products.…”
Section: Identified Components Variation Proportion (%)mentioning
confidence: 99%
“…A decrease in the level of natural resistance and immunobiological reactivity, against which the conditionally pathogenic microflora manifests its effect, makes it difficult to carry out preventive measures for gastrointestinal and respiratory diseases [2,3]. Moreover, most pathologies of the gastrointestinal and respiratory tracts: gastroenteritis, pneumonia, and with systemic pneumoenteritis, occur with the participation of not one, but several pathogens at the same time [4]. All this implies a significant use of preventive and therapeutic agents, cyclicity, and rotation in their application, the development of new treatment and prevention schemes for various diseases, as well as the creation on their basis of new resistant compounds with a potentiated, synergistic antimicrobial effect, addiction to which will become unlikely, and the therapeutic and preventive effect, is much higher [5,6].…”
Section: Introductionmentioning
confidence: 99%